Kinetics of CH3COOOH Formation from CH3COOH + H2O2 Reaction in the Presence of H+ Ion - Ngoc Duy, Vu (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2, 2018)
Kinetics of peracetic acid formation in the reaction between acetic acid and hydro peroxide was investigated in this study. Experiments were conducted in a batch-reactor with a solution volume of 50 mL at 25 ± 1 o C. Concentrations of acetic acid and hydro peroxide are 10.5 M and 4.2 M, respectively.  The effect of H + ion on the reaction was evaluated in the range from  0.036 to 0.72 M. The formation of peracetic acid was followed by iod - thiosulfate titration with starch indicator. Experimental data were analyzed using reversible first - order rate law to get reaction orders of H + and H 2 O 2 to be 1.        Keywords Peracetic acid, acetic acid, hydro peroxide, kinetics, catalyst References [1] Mehmet Kitis, Disinfection of wastewater with peracetic acid: a review, Environment International, 30 (2004) 47. [2] Polonca Preša and Petra Forte Tavčer, Low Water and Energy Saving Process for Cotton Pretreatment, Textile Research Journal, 79 (1) (2009) 76. [3] V, Lazarova, M, L, Janex, L, Fiksdal, C, Oberg, I, Barcina, M, Pommepuy, Disinfection technologies: short and long term efficiency, Wat, Sci, Tech, 38 (12) (1998) 109. [4] Silvano Monarca, Donatella Feretti, Carlo Collivignarelli, Licia Guzzella, Ilaria Zerbini, Giorgio Bertanza, Roberta Pedrazzani, The influence of different disinfectants on mutagenicity and toxicity of urban wastewater, Wat, Res, 34 (17) (2000) 4261. [5] ZHAO Xue-bing, ZHANG Ting, ZHOU Yu-jie, LIU De-hua, Preparation of Peracetic Acid from Acetic Acid and Hydrogen Peroxide: Experimentation and Modeling, The Chinese Journal of Process Engineering, 8(1) (2008) 35.